2020
DOI: 10.1016/j.jamcollsurg.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Propensity Score Methodology in Contemporary High-Impact Surgical Literature

Abstract: BACKGROUND: Propensity score (PS) analysis is a statistical method commonly used in observational trials to account for confounding. Improper use of PS analysis can bias the effect estimate. The aim of this study is to review the use and reporting of PS methods in high-impact surgical journals with a focus on propensity score matching (PSM). STUDY DESIGN: The 10 surgical journals with the highest impact factors were searched to identify studies using PS analysis from January 1, 2016 to December 14, 2018. We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
(62 reference statements)
3
22
0
Order By: Relevance
“…Disagreements regarding exclusion criteria were resolved by a third-party with an advanced degree in epidemiology or biostatistics. Reporting quality was defined using guidelines adapted from Yao et al and Grose et al which have previously been used to evaluate PSM methodology in a variety of other fields [14,16,19,21]. The following study characteristics were recorded: journal, journal impact factor, subspecialty, year, initial sample size, matched sample size, and collaboration with a statistician.…”
Section: Data Extraction and Outcomes/measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Disagreements regarding exclusion criteria were resolved by a third-party with an advanced degree in epidemiology or biostatistics. Reporting quality was defined using guidelines adapted from Yao et al and Grose et al which have previously been used to evaluate PSM methodology in a variety of other fields [14,16,19,21]. The following study characteristics were recorded: journal, journal impact factor, subspecialty, year, initial sample size, matched sample size, and collaboration with a statistician.…”
Section: Data Extraction and Outcomes/measuresmentioning
confidence: 99%
“…Additionally, we recorded whether studies found statistically significant results for their primary outcome. If the primary outcome PLOS ONE was unclear, the outcome given the most attention in the discussion section by the length of text it was examined was selected [21]. PSM reproducibility was assessed based on inclusion of four reporting criteria as established by Lonjon et al and others [14,[24][25][26][27]: (1) the algorithm used for matching; (2) the matching ratio; (3) whether replacement was used in the matching process (4) whether the statistical tests used to compare PSM groups assumed independent or paired groups.…”
Section: Data Extraction and Outcomes/measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…When some discrepancies exited, we resolved them by making discussions or consulting with a third author. The items based on previously literatures [2,3,10] were critically adopted to extract information. The general characteristics of included articles contained year of publication, name of journal, origin region of first author, author's affiliations, participation of statistician or epidemiologist in author ( identified from author's affiliations or the acknowledgements part ), international cooperation, journal source of Science Citation Index(SCI), impact factors(IF), number of citations, number of pages, number of authors, funding of support, the way to determine the sample size and number of patients engaged.…”
Section: Data Extractionmentioning
confidence: 99%
“…As a widely used statistical method, the PS may control confounding factors by conditioning the probability of receiving the treatment of each participants. It performed better than multivariable regression in terms of randomized design, because the PS precluded those patients who have no similar distributions in groups[1] and it was not limited by the total sample size [2]. The PS also allows researchers to better understand the potential impact of medical interventions and complement the findings of observational studies.…”
Section: Introductionmentioning
confidence: 99%